2021
DOI: 10.1590/0103-8478cr20200740
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus availability and uptake by mycorrhizal and non-mycorrhizal plants in an onion no-tillage system

Abstract: Onion is an important vegetable crop, predominantly grown under conventional tillage system management. Alternatively, the vegetable no-tillage system uses cover crops to form a residue layer, which improves soil physical, chemical, and biological attributes. Aiming to understand the interaction of mycorrhizal and non-mycorrhizal cover crops, phosphatase activity, and soil phosphorus availability and uptake by plants, a no-tillage vegetable production system experiment with onion was carried out in Ituporanga,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In natural systems with no addition of phosphorus, P availability is related to the cycling of organic P. In fertilized soils, most available phosphorus is buffered by labile inorganic fractions (NOVAIS; SMITH, 1999). Thus, considering the addition of P fertilizers in the BO-F area, the results may be related to inorganic and organic P accumulations with different binding energy levels (SANTOS et al, 2008). Means followed by the same letter in the columns are not different by the Bonferroni test (p<0.05).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In natural systems with no addition of phosphorus, P availability is related to the cycling of organic P. In fertilized soils, most available phosphorus is buffered by labile inorganic fractions (NOVAIS; SMITH, 1999). Thus, considering the addition of P fertilizers in the BO-F area, the results may be related to inorganic and organic P accumulations with different binding energy levels (SANTOS et al, 2008). Means followed by the same letter in the columns are not different by the Bonferroni test (p<0.05).…”
Section: Resultsmentioning
confidence: 97%
“…According to Silva et al (2011), poultry litter is a good source of nutrients that can substitute chemical P fertilization when properly managed. The organic and inorganic soil phosphorus fractions can be a source or drain for the soil solution, depending on their mineralogical characteristics, environmental conditions, soil fertilization, and soil management (SANTOS et al, 2008). In natural systems with no addition of phosphorus, P availability is related to the cycling of organic P. In fertilized soils, most available phosphorus is buffered by labile inorganic fractions (NOVAIS; SMITH, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…4) to support mycorrhizal infection. Ventura et al (2021) conducted an onion with no-tillage cultivation system after the cultivation of mycorrhizal cover crops of black oats and rye. They reported that the root mycorrhizal colonization rate was higher after rye cover cropping than under oilseed radish (non-mycorrhizal plant) cover cropping.…”
Section: The Average Ofmentioning
confidence: 99%